Far-Field Tsunami Impact in the North Atlantic Basin from Large Scale Flank Collapses of the Cumbre Vieja Volcano, La Palma - Tehranirad, Babak; Harris, Jeffrey C.; Grilli, Annette R.; Grilli, Stephan T.; Abadie, Stéphane; Kirby, James T.; Shi, Fengyan (Pure and Applied Geophysics, 2015)
International audience